The sixes ebook A novel. - White, Kate (2011)
Phoebe Hall's Manhattan life is unexpectedly derailed off the fast track when her long-term boyfriend leaves her just as she is accused of plagiarizing her latest bestselling celebrity biography. Looking for a quiet place to pick up the pieces, Phoebe jumps at the offer to teach at a small private college run by her former boarding school roommate and close friend Glenda in a sleepy Pennsylvania town. But behind the campus's quiet cafés and looming maple trees lies something darker. The body of a junior co-ed washes up from the nearby river, and soon rumors begin to swirl of of past crimes and abuses wrought by a disturbing secret society known as The Sixes. Determined to find answers and help Glenda, Phoebe secretly embarks on a search for clues—a quest that soon raises dark memories of her own boarding school days. Plunging deeper into danger with every step, Phoebe knows she's close to unmasking a killer. But with truth comes a deeply terrifying revelation: the past can't be outrun . . . and starting over can be a crime punishable by death.